5th International Symposium on High Temperature Metallurgical Processing : proceedings of a symposium sponsored by the Minerals, Metals & Materials Society (TMS) held during TMS 2014, 143rd Annual Meeting & Exhibition, San Diego Convention Center, San Diego, California, USA - Jiang, Tao (Wiley, 2014)
The analysis, development, and/or operation of high temperature processes that involve the production of ferrous and nonferrous metals, alloys, and refractory and ceramic materials are covered in the book. The innovative methods for achieving impurity segregation and removal, by-product recovery, waste minimization, and/or energy efficiency are also involved. Eight themes are presented in the book: 1: High Efficiency New Metallurgical Technology2: Fundamental Research of Metallurgical Process 3: Alloy and Materials Preparation 4: Roasting, Reduction, and Smelting5: Si.